The effect of endovascular baroreflex amplification on central sympathetic nerve circuits and cerebral blood flow in patients with resistant hypertension: A functional MRI study - Groenland, Eline H.; van Kleef, Monique E. A. M.; Hendrikse, Jeroen; Spiering, Wilko; Siero, Jeroen C. W. (Frontiers in Neuroimaging, 2022)
Background: Endovascular baroreflex amplification (EVBA) by implantation of the MobiusHD is hypothesized to lower blood pressure by decreasing sympathetic activity through the mechanism of the baroreflex. In the present study we investigated the impact of MobiusHD implantation on central sympathetic nerve circuits and cerebral blood flow (CBF) in patients with resistant hypertension. Materials and Methods: In thirteen patients, we performed blood oxygenation level-dependent functional magnetic resonance imaging (BOLD fMRI) at rest and during Valsalva maneuvers, before and 3 months after EVBA. Data were analyzed using a whole-brain approach and a brainstem-specific analysis. CBF was assessed using arterial spin labelling MRI. Results: Resting-state fMRI analysis did not reveal significant differences in functional connectivity at 3 months after EVBA. For the Valsalva maneuver data, the whole-brain fMRI analysis revealed significantly increased activation in the posterior and anterior cingulate, the insular cortex, the precuneus, the left thalamus and the anterior cerebellum. The brainstem-specific fMRI analysis showed a significant increase in BOLD activity in the right midbrain 3 months after EVBA. Mean gray matter CBF (partial volume corrected) decreased significantly from 48.9(9.9) ml/100gr/min at baseline to 43.4(13.0) ml/100gr/min (p=0.02) at 3 months. Conclusions: This first fMRI pilot study in patients with resistant hypertension treated with EVBA showed a significant increase in BOLD activity during the Valsalva maneuver in brain regions related to sympathetic activity. No notable signal intensity changes were observed in brain areas involved in the baroreflex circuit. Future randomized controlled studies are needed to investigate whether the observed changes are directly caused by EVBA.